Long-Term Trends and Variability of Water Levels and Tides in Buenos Aires and Mar del Plata, Argentina - Santamaria-Aguilar, Sara; Schuerch, Mark; Vafeidis, Athanasios T.; Carretero, Silvina C. (Frontiers in Marine Science, 2017)
We present an analysis of the long-term trends and variability of extreme water and tidal levels and the main tidal constituents using long-term records from two tide gauges in the wider region of the Rio de la Plata estuary: Buenos Aires (1905-2013) and Mar del Plata (1956-2013). We find significant long-term trends in both tidal levels and the main tidal constituents (M2, S2, K1, O1 and the overtide M4) from a running harmonic analysis in both locations. The tidal range decreased on average 0.63 mm y-1, as a result of an increase of the low water levels and a decrease of the high water levels. We also find a secular decrease in the amplitude of the semi-diurnal constituents and an increase of the diurnal ones, but of different magnitudes at each location, which suggests that different processes are producing these changes. In Buenos Aires, an increase of river discharge into the estuary seems to reduce the tidal range by hampering the propagation of the tidal wave into the estuary, whereas no influence of river discharge on water and tidal levels can be detected in Mar del Plata. We believe that other factors such as thermohaline changes or the rise of mean sea-level may be responsible for the observed tidal range decrease. Despite the tidal long-term trends, we find no significant trends in the meteorological component of the tide-gauge records other than an increase in the mean sea-level. In addition, we explore teleconnections between the variability of the meteorological component of the tide-gauge records and climate drivers.